Almost home : reforming home and community care in Ontario - Baranek, Patricia M. (University of Toronto Press, 2004)
"Almost Home is a comprehensive study of the policy questions underlying the shift in medical care from hospitals to homes and communities, a change that is reshaping Canadian health care policy and politics. Using document analysis and interviews with government officials and other key stakeholders in the policy community, the authors analyse the policy content and process of five different attempts to reform home and community care in Ontario between 1985 and 1996, as introduced by Liberal, New Democratic, and Conservative governments."--Jacket